Neurovascular Structures at Risk With Curved Retrograde TTC Fusion Nails. (October 2017) - de Cesar Netto, Cesar; Johannesmeyer, David; Cone, Brent; Araoye, Ibukunoluwa; Hudson, Parke William; Sahranavard, Bahman; Johnson, Michael; Shah, Ashish
Background: The purpose of this study was to assess the risk of iatrogenic injury to plantar neurovascular structures of the foot during insertion of a curved retrograde tibiotalocalcaneal (TTC) fusion nail. Material and Methods: Ten below-knee thawed fresh-frozen cadaveric specimens underwent curved retrograde nailing of the ankle. The shortest distance between the nail and the main plantar neurovascular branches and injured structures were recorded during dissection. We also evaluated the relative position of these structures along 2 lines (AB, connecting the calcaneus to the first metatarsal, and BC, connecting the first and fifth metatarsal). Results: The lateral plantar artery was found to be in direct contact with the nail 70% of the time, with a macroscopic laceration 30% of the time. The Baxter nerve was injured 20% of the time, as was the lateral plantar nerve. The medial plantar artery and nerve were never injured. The most proximal structure to cross line AB was the Baxter nerve followed by the lateral plantar artery, the nail, the lateral plantar nerve, and the medial plantar nerve. Conclusion: Our cadaveric anatomic study found that the most common structures at risk for iatrogenic injury by lateral curved retrograde TTC fusion nails were the lateral plantar artery and nerve, and the Baxter nerve. Clinical Relevance: Determination of a true neurovascular safe zone is challenging and therefore warrants careful operative dissection to minimize neurovascular injuries.